2011
DOI: 10.1055/s-0031-1286271
|View full text |Cite
|
Sign up to set email alerts
|

Früherkennung von Brust- und Gebärmutterhalskrebs – ein systematischer Review zu Wissen, Einstellungen und Inanspruchnahmeverhalten der Frauen in Deutschland

Abstract: The interviewees' substantial lack of knowledge underscores the need for optimising communication on the aims, benefits and risks of screening tests to enable women to make an informed decision. It is desirable to continuously monitor women's knowledge about and participation in screening and determinants thereof with a view to laying the foundations for target group-specific information strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
7
1
Order By: Relevance
“…Furthermore, younger patients in Germany are diagnosed more often with early tumour stages [14]. While other studies have shown that more advanced tumour stages are mainly found in older patients [13,15], this could not be confirmed by the present data. The literature reports contradictory findings on the influence of age on prognosis: While Kumar et al has observed an influence in his SEER data analysis [5], others did not [16].…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…Furthermore, younger patients in Germany are diagnosed more often with early tumour stages [14]. While other studies have shown that more advanced tumour stages are mainly found in older patients [13,15], this could not be confirmed by the present data. The literature reports contradictory findings on the influence of age on prognosis: While Kumar et al has observed an influence in his SEER data analysis [5], others did not [16].…”
Section: Discussioncontrasting
confidence: 96%
“…This may be due to the fact that younger women pay more attention to their bodies or participate more regularly in PAP-smear screening for cervical cancer [13], during which incidental vulvar carcinomas could be discovered by the examining gynaecologist.…”
Section: Discussionmentioning
confidence: 99%
“…In 2002–04, 45.3% of women aged 55 years or older residing in Saarland reported to have had a mammography within the last two years (unpublished data from the population-based ESTHER cohort study in Saarland [43,44]). For 2007–08, a proportion of 53% of eligible women participating in the organized screening was reported [45,46]. …”
Section: Discussionmentioning
confidence: 99%
“…The results lead to the assumption that participants with higher health literacy have less information needs regarding questions about follow-up care after the acute treatment, questions about the use of long-term side effects and about heredity of breast cancer. Furthermore, a lower level of health literacy is linked with inadequate patient-physician communication [24][25][26]. Regarding questions about the subject heredity of breast cancer, it seems hardly surprising that respondents with children have a significantly increased likelihood of unmet information needs [27].…”
Section: Main Findingsmentioning
confidence: 99%
“…Important considerations can be explained due to the inclusion of the patients' characteristics. It seems, in addition to the level of health literacy, school education, age, and language skills of the respondents, that the kind of realized information deficiency and the demanded offers also play a vital role in this matter [24,29]. A single follow-up care plan that provides appropriate patient-centered information for the patient can contribute at best to reduce the unmet information needs [30].…”
Section: Main Findingsmentioning
confidence: 99%